(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The level of employee discipline must always be considered by the company so that their actions remain on the predetermined path. It is expected that this research can determine the influence of leadership style, motivation, and organizational culture on employee work discipline at UD. Putra Bali Glass Gianyar. The entire population is used as a sample with a fixed number of 32 people selected with a saturated sample. Data analysis using multiple linear regression. The data analysis conducted shows that both partially and simultaneously, leadership style, motivation, and organizational culture are able to influence employee work discipline at UD. Putra Bali Glass Gianyar positively and significantly. Suggestions from the results of this study are to always maintain employee work discipline by considering factors of leadership style, motivation, and organizational culture